ANALISIS KEMAMPUAN REPRESENTASI FREE BODY DIAGRAMS DALAM MENYELESAIKAN SOAL SOAL APLIKASI HUKUM NEWTON PADA SISWA MA DAREL HIKMAH PEKANBARU - Fitri Novianti; Mitri Irianti; Azhar ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to describe the ability of free-body representation diagrams MA Darel Hikmah students in solving Newton's Law application problems. The research used is a survey method. The population is all students of class X MA Darel Hikmah Pekanbaru, namely: class X1, class X2, class X3 which amounted to 67 students, while the sample determined using slovin formula with error rate of 5% of the population then, the sample of 57 students. The results obtained mean score for the ability to determine the forces acting on the object of 7257.5%, for the ability to determine the forces acting on the object of 60.55% and for ability to determine the forces that work against the x and y axis Of 4122.5. Thus the ability of representation of free body diagrams of class X student Darel Hikmah is in very low category.Key Words: The nature of Physics learning, The ability of free body diagrams representation